Development of a lightweight IoT security system - Abdullah Assaig, Faisal Ahmed; Khalifa, Othman Omran; Gunawan, Teddy Surya; Halbouni, Asmaa Hani; Hamidi, Eki A.Z; Ismail, Nanang (IEEE, 2022)
Especially for constrained node devices, the risk of security and privacy increases as the number of Internet of Things (IoT) devices increases. From smart homes to smart cities, IoT is ubiquitous, indicating that most devices will be connected to the internet soon. This exacerbates the problem of securing IoT devices. Where our privacy is at risk are IoT devices with inadequate security. These devices transmit sensitive and private data. To construct well-secured IoT devices, we must first overcome IoT device issues such as low computation power, small data storage, and low power consumption. This demonstrates the need for IoT device security systems to be lightweight. However, there is currently no adequate security system for IoT devices with limited functionality. Consequently, the objectives of this paper are to design a secure IoT system and to analyze the overall system’s power consumption and latency. The lightweight security system was able to secure MQTT messages with a latency of 0.3s and power consumption of 1.683mJ, according to the obtained results. Therefore, the success of the paper will enable IoT devices with limited bandwidth to transmit data securely.